ACCESS TO INFORMATION ON THE STATE OF THE ENVIRONMENT - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In this article the author provides analysis of the provisions of the European Directive on Environmental Information from 2003 presently in force, and provisions for their implementation in the legislation of the Republic of Serbia, in particular the current Environmental Protection Law from 2009. Attention has been paid to the relevant rules of the Aarhus Convention on Environmental Information ratified into law of the Republic of Serbia in 2009. The author finds that majority of provisions of the European Directive on Environmental Information have been implemented into the legislation of the Republic of Serbia, however the author notes that instead of restrictive interpretation of the refusal to provide access to information on the state of the environment, as envisaged by the European Directive, the law of the Republic of Serbia provides for a wide range of reasons for refusing access to information regarding the environment. Further, the article offers analysis of procedures for providing legal protection, especially before the court (state courts or arbitral tribunals) in cases of wrongful refusal to provide access to requested information by the competent state organ, both at national and regional level. The author also notes that, contrary to the European Directive which does not require a need to demonstrate legal interest in order to obtain information on the state of the environment, the law of the Republic of Serbia imposes such requirement. Truth be told, the Aarhus Convention on Access to Information in Environmental Matters that has been ratified by the Republic of Serbia, requires applicants to prove or to state the existence of the legal interest.